SYNERGIZING ERGONOMIC WORK SYSTEMS WITH ISO 9001:2015 QUALITY MANAGEMENT IN INDUSTRIAL TECHNOLOGY EDUCATION: A PARADIGM OF INNOVATIVE EDUCATIONAL PRACTICES - Safutra, Nur Ihwan; Alisyahbana, Takdir; Fole, Asrul; Sumir, Devina; Magfirahwati, Magfirahwati (Komunitas Menulis dan Meneliti (Kolibi), 2024)
This study examines the integration of ergonomic work systems and the ISO 9001:2015 standard in the context of industrial technology education at FTI-UMI. The main focus is to understand the impact of ergonomic work systems on student satisfaction, highlighting aspects such as organizational conditions, learning processes, physical environment, academic services, student research activities, and facilities. Through a qualitative and case study approach, the research shows the significant contribution of ergonomic aspects to student satisfaction, with proposed improvements including enhancing classroom facilities, hotspot services, and academic services. Findings also emphasize the importance of intensive communication, improving learning processes, and enhancing service quality. In conclusion, the integration of ergonomic work systems and ISO 9001:2015 can enhance operational efficiency, service quality, and responsiveness to environmental changes in educational institutions, providing valuable insights for institutions and students to enhance learning experiences and performance in the academic environment.